Tafsir Youtubi: - Abidin, Ahmad Zainal; Chayati, Dewi Charisun (SUHUF, 2022)
The Youtube social media platform has given birth to a new form of Qur'anic exegesis, which is known as the Youtube interpretation. KH. Ahmad Baha'uddin Nursalim (Gus Baha') can be called a Youtube mufasir because his name has become increasingly known since the video of the recitation of his commentary that was uploaded by his lovers (muhibbin) on the Youtube channel. Among the videos of these commentary lectures, Gus Baha's commentary on who can be called a follower of Prophet Isa based on surah Ali 'Imran/3: 55 is interesting and important to study because Gus Baha' rejects the interpretation contained in the book of Jalalain commentary. This analytical descriptive research is virtual ethnographic in nature, so the data comes from the online environment, namely recordings of Gus Baha's interpretation of recitations uploaded on the Youtube channel. Then the data was analyzed. it was found that Gus Baha' rejected the mainstream interpretation in society that Christians are followers of the prophet Isa. This rejection was based on the deviation they did.